Using fMRI to Assess Brain Activity in People With Down Syndrome: A Systematic Review - Carbó-Carreté, Maria; Cañete-Massé, Cristina; Peró-Cebollero, Maribel; Guàrdia-Olmos, Joan (Frontiers in Human Neuroscience, 2020)
Background In the last few years, many investigations have focused on the study of brain activity in general and pathological population using non-invasive techniques such as EEG, PET, fMRI or MRI. However, the study of the use of non-invasive registers of brain signal for evaluating the cognitive activity of people with Down Syndrome (DS) has not been sufficiently addressed. The objective is describe the state of the art on the use of brain signal recorded with functional magnetic resonance imaging (fMRI) in research with people with DS. Method A systematic review has been done based on PRISMA recommendations, and only nine papers on this topic have been published. Two independents researchers select all relevant information of each paper. Analyses of information concordance shown a higher value of agreement between researchers. Results Although at this moment there are few works published, the use of fMRI in people with DS are becoming an appropriate option for the study of brain functioning in this population. Of the nine papers localized, five use task design and four resting state paradigms. Conclusion Thus, we emphasize the need to incorporate rigorous cognitive activity procedures in the DS population. We suggest several factors that must be considered when designing an fMRI register with a task or resting paradigm in a DS population.